A vacancy‐rich, partially inverted spinelloid silicate, (Mg, Fe, Si)2(Si, □)O4, as a major matrix phase in shock melt veins of the Tenham and Suizhou L6 chondrites. (7th July 2019) - Ma, Chi; Tschauner, Oliver; Bindi, Luca; Beckett, John R.; Xie, Xiande
Abstract: A new high‐pressure silicate, (Mg, Fe, Si)2 (Si, □)O4 with a tetragonal spinelloid structure, was discovered within shock melt veins in the Tenham and Suizhou meteorites, two highly shocked L6 ordinary chondrites. Relative to ringwoodite, this phase exhibits an inversion of Si coupled with intrinsic vacancies and a consequent reduction of symmetry. Most notably, the spinelloid makes up about 30–40 vol% of the matrix of shock veins with the remainder composed of a vitrified (Mg, Fe)SiO3 phase (in Tenham) or (Mg, Fe)SiO3 ‐rich clinopyroxene (in Suizhou); these phase assemblages constitute the bulk of the matrix in the shock veins. Previous assessments of the melt matrices concluded that majorite and akimotoite were the major phases. Our contrasting result requires revision of inferred conditions during shock melt cooling of the Tenham and Suizhou meteorites, revealing in particular a much higher quench rate (at least 5 × 10 3 K s −1 ) for veins of 100–500 μm diameter, thus overriding formation of the stable phase assemblage majoritic garnet plus periclase.